Internet and female victimization - Zunic, Natalija; Vilic, Vida (Temida, 2018)
The subject of this paper is a gender analysis of female victimization in the cyberspace. Since the Internet appears as a global network, it gives a global dimension to the virtual space, connecting any two points on the planet through a cyberspace. From this dimension, the cyberspace is also perceived as a social space. Namely, the Internet and social networks provide a continuous and unlimited place for users? gathering and contact, indicating that, potentially, each user is a potential victim. When analyzing victimization in the cyberspace it is important to notice that anonymity encourages perpetrators and increases insecurity of the victim. Research findings indicate that sexist and misogynistic attitudes towards women on social networks result in their exclusion, marginalization and/or victimization on the internet. The feminist criticism also points out that not only matters whether something is considered to be legal or illegal behaviour, but that cyber victimization is a continuous manifestation of misogynistic attitudes that are part of the dominant gender and cultural ideologies. The aim of this paper is to present the basic phenomenological and etiological characteristics of gender dimensions of the use/misuse of information technologies and to show that virtual communication, according to its social consequences, is not gender neutral and that cyber violence has its own gender implications. The data indicates that in the digital world, the privacy of women is significantly compromised and associated with new and terrifying forms of on-line violence. Feminist researchers warn that ?the Internet is only the culture accelerator, to which we are all accustomed, and its name is the patriarchate.? From this cognitive perspective, victimization of women on social networks mainly depends on the level of the patriarchal ideology of gender in a society, the influence of the media and the protection of women? s rights. Women can experience various forms of violence and privacy violations on the social networks, such as hate speech, spreading lies, stalking, photo montage, creating of false user profiles, the continuation of family violence, threats and blackmail, etc. The main topics discussed in this paper relate to general approach to the phenomenon of cyberspace and cyber violence; various types of cyber violence; cultural context and gender dimension of on-line victimization; various forms of cyber violence against women; specific characteristics of female victimization in on-line communication and the perception of preventing female victimization on the Internet, in the context of spreading gender- sensitive social norms and values through legal standardization and socialization of women? s rights. nema